Pelatihan Kader Dalam Pemanfaatan Aroma Terapi Terhadap Penurunan Kecemasan Menghadapi Persalinan Pada Ibu Hamil Trimester III - Yeni Wardhani; Ika Wijayanti; Sely Maya Nurul Aeni; Elsa Monalisa Warkawani (Jurnal Pengabdian Ilmu Kesehatan, 2025)
During pregnancy, particularly in the third trimester, anatomical and physiological changes occur that lead to both physical and psychological discomforts, such as sleep disturbances and anxiety before childbirth. Anxiety is a normal response in the adaptation process, characterized by feelings of worry or uneasiness about uncertain outcomes. If left unaddressed, anxiety can trigger depression. One non-pharmacological method to reduce anxiety is aromatherapy, a therapeutic approach using essential oils known for their calming effects and ability to improve physical and psychological well-being. Essential oils possess various pharmacological properties, including antibacterial, sedative, and vasodilator effects. However, interviews revealed that the community especially pregnant women has not yet utilized natural remedies such as aromatherapy to manage pregnancy discomforts. Through community service activities, educational sessions and demonstrations were conducted on the benefits of aromatherapy in reducing anxiety before childbirth in third-trimester pregnant women. The results showed an increase in health cadres' knowledge. Prior to the intervention, only 35% of cadres had good knowledge, which increased to 65% after the intervention. Meanwhile, those with poor knowledge decreased from 40% to 10%. This indicates that educational sessions effectively enhanced understanding of the use of aromatherapy for pregnant women.